POTENSI BEBERAPA SUMBER KARBOHIDRAT SEBAGAI BAHAN DASAR PEMBUATAN BIOETANOL MELALUI FERMENTASI - Rahman, Fathur; Mahrus, Muhammad Haissul; Fahmi, Miraz’hul; Pratama, Riansyah Dimas; Aswat, Muhammad Raihan; Rizkirullah, Muhammad Aditya; Kartika, Rudi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
This literature review aims to determine the potential of various carbohydrate sources as raw materials for bioethanol production through fermentation to achieve maximum ethanol concentration. The hydrolysis process is conducted enzymatically using microbes during the liquefaction stage and gluco-amylase during the saccharification stage, followed by fermentation by microbes. The literature results show that the carbohydrate source, Ganyong tuber (Canna edulis Kerr.), produces a maximum ethanol concentration of 84.451% with a fermentation period of 7 days. Keywords: Bioethanol, Fermentation, Hydrolysis, Carbohydrate